Association between anger management and cigarette consumption in adolescents (2016)
Introduction: Cigarette smoking in adolescents is associated with a set of variables such as sex, age, anxiety disorders, depression and secondhand smoke (parents, siblings and friends). However, the association between anger management and smoking among adolescent students has been poorly studied in Colombia.Objective: To quantify the association between anger management in high school students in Cartagena, Colombia.Materials and methods: A cross-sectional survey designed for adolescent students of sixth and seventh grade in high school. Anger management was quantified through a seven-item version of the Spielberger’s Inventory for State-Trait Anger Expression (Cronbach’s alpha: 0.73) and through the input of the participants who have smoked at least once.Results: A total of 1 090 students between ages 10 to 18 (µ=12.3, σ=1.1), attending sixth and seventh grades, took part in the study; 565 (52.1%) were female. A group of 269 students (24.7%) reported low anger control, and 127 (11.7%) stated they had smoked at least once. After age and sex adjustment, the association between anger and smoking was not statistically significant (OR=1.35; 95%CI: 0.89-2.04).Conclusions: Anger management is a variable independent from cigarette smoking among teenager students.